155k views
4 votes
Someone please..

Solve the system of equation by using the linear combination method. Explain each step in solving using the linear combination method. Show all of your work.

2x + 3y = 1

y= -2x - 9

User Loeschg
by
5.3k points

1 Answer

5 votes

Answer:

x = -7, y = 5

Explanation:

Sub the value of y into the first equation

2x + 3(-2x - 9) = 1

2x - 6x - 27 = 1

-4x -27 -1 = 0

-4x - 28 = 0

-4x = 28

x = 28 / (-4)

x = -7

Sub the x value into the second equation

y = -2 * (-7) - 9

y = 14 - 9

y = 5

User Novellizator
by
5.3k points